Activism on the web everyday struggles against digital capitalism - Barassi, Veronica (Routledge new developments in communication and society research, 2015)
Activism on the Web examines the everyday tensions that political activists face as they come to terms with the increasingly commercialized nature of web technologies and sheds light on an important, yet under-investigated, dimension of the relationship between contemporary forms of social protest and internet technologies